Efficacy and safety of indigo naturalis oil extract (Lindioil ointment) for the treatment of atopic dermatitis: a randomized, crossover, evaluator-blinded, controlled trial - Yang, Chin-Yi; Chen, Chun-Bing; Lu, Chun-Wei; Chi, Min-Hui; Wu, Jennifer; Chung, Wen-Hung; Lee, Be-Han; Lin, Yin-Ku (Frontiers in Pharmacology, 2025)
IntroductionLindioil ointment or its compound formulations are commonly used traditional Chinese medicine practitioners to treat adult eczema or localized dermatitis. This study aimed to determine the efficacy and safety of Lindioil ointment (indigo naturalis oil extract) for treating atopic dermatitis (AD).MethodsThis was a prospective, randomized, crossover, evaluator-blinded, controlled study. Twenty-two patients with a median age of 26.5 (range, 20.8–44.3) years were treated with Lindioil or tacrolimus 0.1%. The primary outcome was change in the eczema areas severity index (EASI), body surface area (BSA), pruritus numeric rating scale (NRS) and dermatology life quality index (DLQI) after each 6-week treatment.ResultsAfter 6 weeks of treatment, the EASI decreased significantly from 6.6 to 3.4 (P = 0.017) in the Lindioil group, and from 6.7 to 1.9 (P < 0.001) in the tacrolimus group. The BSA percentage change was significantly less in the tacrolimus group (−43.6% vs. −86.7%, P = 0.002). Significant differences between the 2 groups were observed in NRS (−2.5 vs. −5.5, P = 0.005) and DLQI median change (−5 vs. −10, P = 0.005). After Lindioil or tacrolimus ointment therapy, AD lesions' skin microbiota shifted from Firmicutes dominance to Proteobacteria dominance, resembling non-lesion skin. The proportion of Staphylococcus aureus species in AD lesions significantly decreased after both treatments, and was not different from that of non-lesion skin.DiscussionLindioil ointment is effective for the treatment of mild-to-severe AD and has less side effects compared to tacrolimus. Lindioil ointment may alleviate AD by altering skin microbiota.Clinical Trial RegistrationThe study was registered in ClinicalTrials.gov, under the number NCT03614221.